Mitochondrial inhibition as a novel therapeutic approach in drug-resistant cancer - Wolf, Dieter (Henry Stewart Talks, 2017)
Drug resistance in prostate cancer, Role of androgen receptor in prostate cancer, Difficulties in finding new prostate cancer drug targets, Rational behind screening for p27 downregulators, Potential for OXPHOS inhibitors in cancer therapy, SMIP004: p27 downregulator and potential drug